Multi-Criteria Evaluation of Crash Barrier Systems Types - Daniel Macek; Dana Měšťanová (The Baltic Journal of Road and Bridge Engineering)
Improvement of the situation regarding accident rates in the European Union is a subject of an action programme set up by the European Commission and called the European Road Safety Action Programme 2003–2010. The aim of the programme is to lower the number of road fatalities because of road accidents by half. To be successful as far as the fulfilment of the aim is concerned it is necessary to make a right choice of appropriate solutions when designing transport constructions. One possibility is to design appropriate crash barrier systems. The right decision is the matter of the usage of an appropriate type of safety device (for instance, the crash barrier), requires concentration of the essential knowledge and further ability to judge and evaluate thoroughly information available. This article deals with the evaluation of types of crash barriers from the viewpoint of their suitability for communication. The evaluation process covers firstly security aspects, secondly takes into consideration economic aspects and eventually ecological criteria. The aim is to set general priorities when using individual types of crash barriers. By using crash barriers in particular conditions there is fulfilled the effort to protect participants in road traffic from the consequences of traffic accidents. The effort is intended to eliminate losses of lives, to protect the health of those involved in traffic accidents, to minimize losses of the vehicle’s value, losses of the construction substance of a road construction, losses of any tangible property, and last but not least to minimize the impact on the environment in a territory surrounding a particular transport construction.